Intervensi Kesehatan pada Komunitas Miskin Efektivitas Program dan Kebijakan Berdasarkan Literatur - Aslan, Muhamad; Nurwahyuningsih, Nurwahyuningsih; Arisandi, Juliana (JURNAL ILMIAH DETUBUYA, 2024)
This study aims to examine the effectiveness of health intervention programs and policies aimed at poor communities through a Systematic Literature Review (SLR) approach. This study focuses on identifying effective intervention patterns, implementation challenges, and the contribution of contextual and community-based approaches to reducing inequality in access to health services. Data were collected from Dimensions and Scopus databases, with a publication coverage of the last five years (2020–2025), and selection was only carried out on relevant and high-quality scientific articles. The results of the review indicate that social determinants such as income, food security, age, and social status play a significant role in influencing the effectiveness of health interventions. Interventions that are responsive to the local socio-economic context have proven to be more successful in increasing household resilience and access to basic health services. Furthermore, the use of a Sustainable Development Goals (SDGs)-based evaluation approach that integrates big data and community participation is highly recommended to address system complexity and strengthen equitable and sustainable policies.